Debating Humanity Towards a Philosophical Sociology - Chernilo, Daniel (Cambridge University Press, 2016)
The question 'what is a human being?' remains one of the most vexing intellectual tasks. Debating Humanity reconstructs how contemporary sociologists and philosophers - among others, Arendt, Taylor, Archer and Boltanski - understand the key anthropological skills that define our shared membership to the human species.